ANALYSIS OF ASSOCIATIVE SOCIAL INTERACTION BETWEEN LEADERS AND EMPLOYEES AT THE BIAK MARINE RESOURCES AND FISHERIES MONITORING STATION OFFICE, MINISTRY OF MARINE AFFAIRS AND FISHERIES - Laha, Saleh; Aini, Dewi Nurul; Ahmad , Busyairi (Gema Kampus IISIP YAPIS Biak, 2025)
This study explores the social interaction between leaders and employees at the Biak Marine and Fisheries Resources Monitoring Station Office. This topic was chosen because of the importance of social interaction in forming a productive work culture and an inclusive work environment, especially in the context of leadership changes and employee cultural diversity. The purpose of this study is to understand how associative social interaction affects work motivation and team dynamics in the office. The study used a qualitative method with a descriptive approach. Data were collected through direct observation, in-depth interviews with leaders and employees, and relevant literature studies. Data analysis techniques were carried out descriptively qualitatively and interpretively, involving data reduction, grouping, and interpretation. The findings of the study indicate that effective social interaction between leaders and employees plays an important role in creating a positive and productive work culture. Recognition and appreciation from leaders contribute significantly to employee work motivation. The implication of these findings is that leaders need to understand their role in motivating and supporting employees to improve overall team performance. Recommendations for organizational practice include developing policies that support constructive social interaction and increasing initiatives to maintain team spirit. This study provides valuable insights for improving the interaction system and work motivation in the Biak PSDKP environment and opens up opportunities for further research in this field.